The causes of variation in learning and behavior: why individual differences matter - Sauce, Bruno; Matzel, Louis D. (Frontiers in Psychology, 2013)
In a seminal paper written five decades ago, Cronbach discussed the two highly distinct approaches to scientific psychology: experimental and correlational. Today, although these two approaches are fruitfully implemented and embraced across some fields of psychology, this synergy is largely absent from other areas, such as in the study of learning and behavior. Both Tolman and Hull, in a rare case of agreement, stated that the correlational approach held little promise for the understanding of behavior. Interestingly, this dismissal of the study of individual differences was absent in the biologically oriented branches of behavior analysis, namely, behavioral genetics and ethology. Here we propose that the distinction between “causation” and “causes of variation” (with its origins in the field of genetics) reveals the potential value of the correlational approach in understanding the full complexity of learning and behavior. Although the experimental approach can illuminate the causal variables that modulate learning, the analysis of individual differences can elucidate how much and in which way variables interact to support variations in learning in complex natural environments. For example, understanding that a past experience with a stimulus influences its “associability” provides little insight into how individual predispositions interact to modulate this influence on associability. In this “new” light, we discuss examples from studies of individual differences in animals’ performance in the Morris water maze and from our own work on individual differences in general intelligence in mice. These studies illustrate that, opposed to what Underwood famously suggested, studies of individual differences can do much more to psychology than merely providing preliminary indications of cause-effect relationships.